Response to commentaries. (8th December 2017) - Hodder, Ian; Lucas, Gavin
Abstract : We would like to begin by thanking all the commentators for taking the time to read and reflect on our dialogue and offer their own reactions; it can be particularly challenging to insert oneself as a third interlocutor within a dialogue between two people, but as Rizvi remarks at the end of her commentary, the important thing is to keep the conversation going and so what started as a dialogue between two people is now a dialogue between six. As a collection, though, the commentators provide a very diverse set of views and perspectives, which means that picking up common threads is not an easy option. Instead, we will try and respond to each of the commentators in turn, addressing what we see as their key points.